Separator for lithium secondary battery and lithium secondary battery comprising same
By coating the heat-resistant layer and adhesive layer on the lithium battery separator, and using materials such as polyacrylate and inorganic particles, the problem of insufficient shape maintenance and adhesion of the separator at high temperature is solved, and the safety and circulation of the battery are improved. Lifespan characteristics.
Patent Information
- Application Number
- CN202380039077.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-10
- Filing Date
- 2023-04-26
- Publication Date
- 2024-12-20
AI Technical Summary
The existing lithium battery separators are difficult to maintain shape under high temperature conditions, resulting in a decrease in battery safety and cycle life characteristics, and insufficient adhesion to the electrodes, which can easily lead to lithium salt precipitation and short circuit.
The porous base coated separator is used to coat the heat-resistant layer and the adhesive layer. The heat-resistant layer is composed of binders such as polyacrylate and inorganic particles. The adhesive layer is derived from vinyl aromatic monomers and alkyl acrylates. The copolymer is composed of phosphonate monomers, with a weight ratio of 1:1 to 1:6, which enhances the heat resistance and adhesion of the membrane.
It realizes high heat resistance and excellent adhesion of the diaphragm at high temperatures, inhibits lithium salt precipitation, improves the safety and cycle life characteristics of the battery, and enhances the stability of the high-temperature storage.
Smart Images

Figure CN119174044A_ABST
Abstract
Description
Technical Field
[0001] Disclosed are a separator for a rechargeable lithium battery and a rechargeable lithium battery including the separator. Background Art
[0002] The separator for an electrochemical cell is an intermediate film that separates the positive electrode and the negative electrode in the battery and continuously maintains ion conductivity to enable charging and discharging of the battery. However, when the battery is exposed to a high temperature environment due to abnormal behavior, the battery generates heat and starts thermal runaway. Therefore, the separator should have a shut-down function (a function of blocking pores by melting a hot-melt resin) to suppress the ignition of the battery, and should ensure the safety of the battery by maintaining its shape without shrinking even at high temperatures.
[0003] Recently, there has been a demand for higher capacity and higher output of batteries, and there is a trend to apply high nickel-based positive electrode active materials with a nickel content of 90 mol% or more or to manufacture them into a stacked battery structure that is easy to achieve capacity. In addition to high capacity and high output, there is a trend to require battery safety that suppresses battery temperature rise and ignition even at high temperatures.
[0004] For example, when a high-nickel positive electrode active material is used, a large amount of gas may be generated under high temperature conditions, which may lead to problems such as capacity drop or heat generation during cycling, making it more necessary to ensure battery safety. Specifically, when gas is generated in the battery, lithium salts precipitate when the gas is located at the interface between the separator and the electrode, which may cause the pores of the separator to be blocked or short-circuited, and the cycle life may be reduced. Therefore, the separator is required to have ultra-high heat resistance and high adhesion to the electrode. Summary of the invention
[0005] Technical issues
[0006] A separator for a rechargeable lithium battery is provided, which has excellent heat resistance and improved adhesion to an electrode, and a separator for a rechargeable lithium battery is provided, which exhibits excellent adhesion even at low temperature / low pressure and can be used for battery types that cannot be applied to high temperature / high pressure processes, thereby providing a rechargeable lithium battery with improved safety and reliability as well as improved high temperature cycle life characteristics and high temperature storage characteristics.
[0007] Technical Solution
[0008] In an embodiment, a separator for a rechargeable lithium battery includes: a porous substrate; a heat-resistant layer on at least one surface of the porous substrate; and an adhesive layer on the heat-resistant layer, wherein the heat-resistant layer includes a first binder and inorganic particles, the first binder includes polyacrylate, polyacrylic acid, polyacrylonitrile, polyvinyl alcohol, polysulfonic acid, polyacrylamide, polyamide, polyurea, polyurethane, their copolymers or combinations thereof, the adhesive layer includes a second binder and a third binder, the second binder includes a copolymer including a first unit derived from a vinyl aromatic monomer, a second unit derived from an alkyl acrylate and a third unit derived from a phosphonate monomer, the third binder includes a fluorine-based polymer, and the weight ratio of the second binder to the third binder in the adhesive layer is 1:1 to 1:6.
[0009] In another embodiment, a rechargeable lithium battery includes a positive electrode, a negative electrode, the aforementioned separator between the positive electrode and the negative electrode, and an electrolyte.
[0010] Beneficial Effects
[0011] According to the embodiment, the separator for a rechargeable lithium battery achieves ultra-high heat resistance, improves adhesion to an electrode, maintains the shape of the separator during battery operation or high-temperature storage, and inhibits precipitation of lithium salt at the interface between the separator and the electrode, thereby ensuring the safety and reliability of the battery. In addition, a rechargeable lithium battery using such a separator can have improved high-temperature cycle life characteristics and high-temperature storage characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 is a cross-sectional view schematically showing a rechargeable lithium battery.
[0013] Figure 2 is a scanning electron microscope photograph of the surface of the adhesive layer of the separator prepared in Example 1. DETAILED DESCRIPTION
[0014] Hereinafter, specific embodiments will be described in detail so that those skilled in the art can easily implement them. However, the present disclosure may be embodied in many different forms and is not to be construed as limited to the example embodiments set forth herein.
[0015] The terms used herein are for describing the embodiments only and are not intended to limit the present disclosure. Unless the context clearly indicates otherwise, a singular expression includes a plural expression.
[0016] As used herein, "a combination thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like, of components.
[0017] Here, it should be understood that terms such as "includes," "comprising," or "having" are intended to indicate the presence of the presented features, quantities, steps, elements, or combinations thereof, but do not exclude the possibility of the presence or addition of one or more other features, quantities, steps, elements, or combinations thereof.
[0018] In the drawings, the thickness of layers, films, panels, regions, etc., are exaggerated for clarity, and like reference numerals denote like elements throughout the specification. It will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element, or there can be intervening elements. Conversely, when an element is referred to as being "directly on" another element, there are no intervening elements.
[0019] In addition, the "layer" here includes not only a shape formed on the entire surface when viewed from a plan view but also a shape formed on a part of the surface.
[0020] In addition, average particle diameter and average size can be measured by methods well known to those skilled in the art, for example, can be measured by a particle size analyzer, or can be measured by a transmission electron microscope photo or a scanning electron microscope photo. Alternatively, it is possible to measure the size by using a dynamic light scattering method, perform data analysis, count the number of particles in each size range, and calculate the average particle diameter value. As used herein, when no definition is provided in addition, average particle diameter can be or can refer to the diameter (D50) of particles measured by a particle size analyzer and having a cumulative volume of 50% by volume in a particle size distribution.
[0021] Here, “or” should not be interpreted as an exclusive meaning, for example, “A or B” is interpreted as including A, B, A+B, etc.
[0022] Diaphragm
[0023] In an embodiment, a separator for a rechargeable lithium battery is provided, the separator comprising: a porous substrate; a heat-resistant layer on at least one surface of the porous substrate; and an adhesive layer on the heat-resistant layer. The heat-resistant layer and the adhesive layer may be positioned on one surface or both surfaces of the porous substrate. The separator may be referred to as a coated separator.
[0024] The heat-resistant layer includes a first binder and inorganic particles. The first binder includes polyacrylate, polyacrylic acid, polyacrylonitrile, polyvinyl alcohol, polysulfonic acid, polyacrylamide, polyamide, polyurea, polyurethane, copolymers thereof or combinations thereof.
[0025] The adhesive layer includes a second adhesive and a third adhesive, the second adhesive includes a copolymer including a first unit derived from a vinyl aromatic monomer, a second unit derived from an alkyl acrylate, and a third unit derived from a phosphonate monomer, the third adhesive includes a fluorine-based polymer, and a weight ratio of the second adhesive to the third adhesive in the adhesive layer is 1:1 to 1:6.
[0026] The separator can achieve ultra-high heat resistance by including a heat-resistant layer, and for example, the separator can satisfy a dry shrinkage rate of less than 5% at 150° C. and a wet shrinkage rate of less than 15% at 150° C. Therefore, the separator maintains its shape even under high temperature conditions and does not deteriorate performance, thereby improving the cycle life characteristics and safety of the battery.
[0027] In addition, by including an adhesive layer, the diaphragm can achieve excellent adhesion even at low temperature and low pressure, and can exhibit stable and strong adhesion between the diaphragm and the electrode plate. The adhesive layer applied to most diaphragms exhibits adhesion under high temperature and high pressure conditions while being impregnated with an electrolyte, and the adhesion of the diaphragm-negative electrode is generally lower than that of the diaphragm-positive electrode. On the other hand, the adhesive layer according to the embodiment achieves adhesion even at temperatures (e.g., 10°C to 50°C) in the battery manufacturing process, and even at very low pressures due to thickness changes caused by charging and discharging of the battery, and it can also be applied to battery types that are difficult to apply high temperature and high pressure processes. In addition, the diaphragm includes a second binder and a third binder in the adhesive layer at a weight ratio of 1:1 to 1:6, so that both the diaphragm-positive electrode interface and the diaphragm-negative electrode interface with an adhesion of 0.1gf / mm or more under low temperature and low pressure conditions can be achieved, and both the high temperature cycle life characteristics and the high temperature storage characteristics of the battery can be improved.
[0028] For example, in a high-capacity battery using a high-nickel positive electrode active material, a lot of gas is generated in the battery during operation. However, if there is no adhesion or low adhesion between the separator and the electrode plate, lithium salts will precipitate at the interface, causing a sharp drop in capacity or heat generation. On the other hand, the separator according to the embodiment has very excellent adhesion between the positive electrode and the negative electrode, and can inhibit the precipitation of lithium salts at the interface, thereby improving the cycle life characteristics of the battery and effectively improving safety issues such as fire and thermal runaway.
[0029] Porous substrate
[0030] The polyolefin used as a porous substrate material in the diaphragm may be, for example, a homopolymer (such as polyethylene or polypropylene), a copolymer or a mixture thereof. Polyethylene may be low-density, medium-density, high-density polyethylene, and from the viewpoint of mechanical strength, high-density polyethylene may be used. In addition, for the purpose of providing flexibility, two or more types of polyethylene may be mixed. From the viewpoint of achieving both mechanical strength and high air permeability, the weight average molecular weight of polyethylene may be 100,000 g / mol to 12,000,000 g / mol, for example, 200,000 g / mol to 3,000,000 g / mol. Polypropylene may be a homopolymer, a random copolymer or a block copolymer, and may be used alone or in a mixture of two or more. In addition, stereoregularity is not particularly limited, and isotactic polypropylene, syndiotactic polypropylene or atactic polypropylene may be used, but cheap isotactic polypropylene may be used. In addition, additives (such as polyolefins other than polyethylene or polypropylene) and antioxidants may be added to polyolefins.
[0031] The porous substrate may include, for example, a polyolefin (such as polyethylene or polypropylene), and may include a multilayer membrane of two or more layers (such as a polyethylene / polypropylene double-layer membrane, a polyethylene / polypropylene / polyethylene three-layer membrane, a polypropylene / polyethylene / polypropylene three-layer membrane), but is not limited thereto, and any material and structure that can be used as a porous substrate in the art may be possible.
[0032] The porous substrate may include, for example, a diene polymer prepared by polymerizing a monomer composition including a diene monomer. The diene monomer may be a conjugated diene monomer or a non-conjugated diene monomer. For example, the diene monomer may include one or more selected from 1,3-butadiene, isoprene, 2-chloro-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene, chloroprene, vinylpyridine, vinyl norbornene, dicyclopentadiene and 1,4-hexadiene.
[0033] The thickness of the porous substrate may be 1 μm to 100 μm, for example, 1 μm to 30 μm, 5 μm to 20 μm, 5 μm to 15 μm, or 5 μm to 10 μm. If the thickness of the porous substrate is less than 1 μm, it may be difficult to maintain the mechanical properties of the separator, and if the thickness of the porous substrate is greater than 100 μm, the internal resistance of the lithium battery may increase.
[0034] The porosity of the porous substrate may be 5% to 95%. If the porosity of the porous substrate is less than 5%, the internal resistance of the lithium battery may increase, and if the porosity is greater than 95%, it may be difficult to maintain the mechanical properties of the porous substrate.
[0035] The pore size of the porous substrate may be 0.01 μm to 50 μm, for example, 0.01 μm to 20 μm or 0.01 μm to 10 μm. If the pore size of the porous substrate is less than 0.01 μm, the internal resistance of the lithium battery may increase, and if the pore size of the porous substrate is greater than 50 μm, it may be difficult to maintain the mechanical properties of the porous substrate.
[0036] Heat resistant layer
[0037] First binder
[0038] The first binder includes at least one selected from polyacrylate, polyacrylic acid, polyacrylonitrile, polyvinyl alcohol, polysulfonic acid, polyacrylamide, polyamide, polyurea, polyurethane and copolymers thereof. The first binder may be applied to the heat-resistant layer together with inorganic particles to provide the separator with high heat resistance.
[0039] Here, acrylic acid has a concept including methacrylic acid and acrylic acid, and polysulfonic acid is a polymer derived from a monomer including a sulfonic acid group, such as polyacrylsulfonic acid, polyacrylamidesulfonic acid, polyvinylsulfonic acid, polyallylsulfonic acid, polystyrenesulfonic acid, polyanetholesulfonic acid, and the like.
[0040] The first binder may include, for example, a homopolymer or copolymer of polyacrylamide, or a copolymer of polyacrylamide and polysulfonic acid.
[0041] For example, the first binder may include a copolymer including a first unit derived from (meth) acrylamide, a second unit derived from a monomer comprising a sulfonic acid group, and a third unit derived from (meth) acrylic acid, (meth) acrylate, a monomer comprising a nitrile group, a monomer comprising an alcohol group, or a combination thereof. The first binder may provide ultrahigh heat resistance for the diaphragm. Here, the unit may be represented as a repeating unit or a structural unit.
[0042] The first unit derived from (meth)acrylamide can improve the adhesion characteristics with the porous substrate through the acrylamide functional group and form hydrogen bonds with the -OH functional group of the inorganic particles, so the inorganic particles in the heat-resistant layer can be more firmly fixed, thereby enhancing the heat resistance of the separator.
[0043] The second unit derived from the monomer containing the sulfonic acid group includes a bulky functional group, thereby reducing the mobility of the copolymer and enhancing the heat resistance of the separator. Here, the sulfonic acid may include a sulfonate. A sulfonate is a salt composed of a sulfonic acid and a suitable cation, which may be, for example, an alkali metal ion. That is, the sulfonate may be an alkali metal sulfonate.
[0044] The monomer containing a sulfonic acid group may include, for example, (meth)acryloylsulfonic acid, (meth)acryloylalkylsulfonic acid, (meth)acrylamidesulfonic acid, (meth)acrylamidealkylsulfonic acid, vinylsulfonic acid, allylsulfonic acid, styrenesulfonic acid, anetholesulfonic acid or salts thereof. Here, the alkyl group may be a C1 to C20 alkyl group, a C1 to C10 alkyl group or a C1 to C6 alkyl group.
[0045] The (meth)acryloylalkylsulfonic acid may be, for example, 2-sulfoethyl (meth)acrylate, 3-sulfopropyl (meth)acrylate, etc., and the (meth)acrylamidoalkylsulfonic acid may be, for example, 2-acrylamido-2-methylpropanesulfonic acid.
[0046] The third unit derived from (meth) acrylic acid, (meth) acrylate, a monomer containing a nitrile group, a monomer containing an alcohol group, or a combination thereof is used to fix the inorganic particles on the porous substrate, and at the same time can provide adhesion, so that the heat-resistant layer can be well adhered to the porous substrate, and can help improve the heat resistance and air permeability of the separator. In addition, the dispersibility of the heat-resistant layer composition can be improved by an acrylic acid group or an alcohol group, and the oxidation resistance of the separator can be increased by a nitrile group and the moisture content can be reduced.
[0047] The (meth)acrylate may include, for example, methyl acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-(perfluorobutyl)ethyl (meth)acrylate, 2-(perfluoropentyl)ethyl (meth)acrylate, 2-(perfluorohexyl)ethyl (meth)acrylate, 2-(perfluorooctyl)ethyl (meth)acrylate, 2-(perfluorononyl)ethyl (meth)acrylate, 2-(perfluorodecyl)ethyl (meth)acrylate, or a combination thereof.
[0048] The monomer containing the nitrile group can be, for example, acrylonitrile, (meth) cyanoalkyl acrylate, or a combination thereof. Here, the alkyl group can be a C1 to C20 alkyl group, a C1 to C10 alkyl group, or a C1 to C6 alkyl group. The (meth) cyanoalkyl acrylate can be, for example, (meth) cyanomethyl acrylate, (meth) cyanoethyl acrylate, (meth) cyanopropyl acrylate, or (meth) cyanooctyl acrylate.
[0049] The monomer comprising an alcohol group may be, for example, vinyl alcohol or olefin alcohol. The alkene alcohol can be, for example, 2-methyl-3-butene-1-ol, 2-ethyl-3-butene-1-ol, 1,1-diphenyl-3-butene-1-ol, 2-methyl-3-butene-2-ol, 2,2-dimethyl-3-butene-1-ol, 3-methyl-1-pentene-3-ol, 2,4-dimethyl-4-pentene-2-ol, 4-alkenyl-2-pentanol, 4-methyl-4-pentene-2-ol, 2-methyl-4-pentene-2-ol, 2-phenyl-4-pentene-2-ol, 2-allylhexamethylenefluoroisopropanol, 2-hydroxy-5-hexene, 3-butene-2-ol, 3-methyl-5-hexene-3-ol, 2-methyl-2-hydroxy-5-hexene, 1-allylcyclohexanol, 2,3-dimethyl-2-hydroxy-5-hexene, 1-heptene-4-ol, and the like.
[0050] In the first binder, the copolymer may include, for example, 55mol% to 99mol% of the first unit, 0.5mol% to 40mol% of the second unit, and 0.5mol% to 40mol% of the third unit. Alternatively, in the first binder, the copolymer may include 75mol% to 94mol% of the first unit, 1mol% to 10mol% of the second unit, and 5mol% to 15mol% of the third unit. Here, the amount range of each unit is based on 100mol% of the copolymer. When the copolymer includes each unit within this range, the first binder can be very firmly bonded to the inorganic particles in the heat-resistant layer, the heat-resistant layer and the porous substrate can be firmly adhered, and by enabling the heat-resistant layer composition to have appropriate viscosity and dispersibility, the heat resistance, chemical resistance, adhesion and processability of the diaphragm can be ultimately improved.
[0051] In the first binder, the copolymer may further include other units in addition to the first to third units, for example, the copolymer may further include diene units, styrene units, ester units, carbonate units, and the like.
[0052] In addition, the copolymer in the first binder may be in various forms, such as an alternating polymer in which units are alternately distributed, a random polymer in which units are randomly distributed, or a graft polymer in which some structural units are grafted.
[0053] The weight average molecular weight of the copolymer of the first binder can be 300,000 g / mol to 970,000 g / mol, for example, 350,000 g / mol to 970,000 g / mol, 450,000 g / mol to 970,000 g / mol or 450,000 g / mol to 700,000 g / mol. In this case, the diaphragm including the first binder in the heat-resistant layer can show excellent adhesion, heat resistance and air permeability. The weight average molecular weight can be the polystyrene conversion average molecular weight measured using gel permeation chromatography.
[0054] The copolymer of the first binder may be prepared by various known methods such as emulsion polymerization, suspension polymerization, block polymerization, solution polymerization or bulk polymerization.
[0055] The first binder may be present in an amount of 1 to 20 wt %, for example, 1 to 15 wt %, 1 to 10 wt %, or 1 to 5 wt %, based on 100 wt % of the heat-resistant layer. When the first binder is included in this range, adhesion and heat resistance of the heat-resistant layer may be improved at the same time.
[0056] Inorganic particles
[0057] The inorganic particles can reduce the possibility of short circuit between the positive electrode and the negative electrode, and prevent the separator from shrinking or deforming sharply due to temperature rise. In other words, the heat-resistant layer can improve the heat resistance and safety of the battery by including the inorganic particles.
[0058] The inorganic particles can be metal oxides, semi-metal oxides or combinations thereof. Specifically, the inorganic particles can include aluminum oxide, titanium dioxide, boehmite, barium sulfate, calcium carbonate, calcium phosphate, amorphous silicon dioxide, crystallized glass particles, kaolin, talc, silicon dioxide-alumina composite oxide particles, calcium fluoride, lithium fluoride, zeolite, molybdenum sulfide, mica, magnesium oxide, etc.
[0059] The inorganic particles can be, for example, Al2O3, SiO2, TiO2, SnO2, CeO2, NiO, CaO, ZnO, MgO, ZrO2, Y2O3, SrTiO3, BaTiO3, MgF2, Mg(OH)2, or a combination thereof. For example, the inorganic particles can be alumina, titanium dioxide, boehmite, barium sulfate, or a combination thereof.
[0060] The inorganic particles may be spherical, plate-like, fibrous, etc., but are not limited thereto, and may be in any form available in the art. Examples of plate-like inorganic particles include alumina and boehmite. Plate-like alumina, boehmite, etc. may improve the heat resistance of the separator, ensure a relatively large number of pores, and improve the physical safety of the lithium battery.
[0061] When the inorganic particles are plate-like or fibrous, the aspect ratio of the inorganic particles can be 1:5 to 1:100, for example, 1:10 to 1:100, 1:5 to 1:50 or 1:10 to 1:50. In addition, the ratio of the length of the major axis to the minor axis on the flat surface of the plate-like inorganic particles can be 1 to 3 or 1 to 2. The aspect ratio and the ratio of the length of the major axis to the minor axis can be measured using an optical microscope. When the aspect ratio and the ratio of the length of the major axis to the minor axis meet the above respective ranges, the thermal shrinkage of the diaphragm can be reduced, a relatively improved porosity can be ensured, and the physical stability of the lithium battery can be improved.
[0062] The average particle size of the inorganic particles may be 0.1 μm to 2 μm, 0.1 μm to 1.5 μm or 0.2 μm to 1.0 μm. The average particle size is measured using a laser scattering particle size distribution meter (e.g., Horiba LA-920) and refers to the median particle size (D50) when the volume is converted to 50% cumulatively from the small particle side. By using inorganic particles having an average particle size within the above range, the bonding force between the heat-resistant layer and the porous substrate can be improved, the appropriate porosity of the separator can be ensured, and the heat resistance and processability of the separator can be improved.
[0063] The weight ratio of the first binder to the inorganic particles in the heat-resistant layer can be 1:20 to 1:40, for example, 1:25 to 1:40, or 1:25 to 1:35. In this case, the heat-resistant layer can achieve very high heat resistance and adhesion. If the weight ratio of the first binder to the inorganic particles is greater than 1:20, the porosity of the coating layer will be reduced due to the excess of the first binder, which will limit the movement of lithium ions, and the moisture absorption of the first binder will increase, resulting in degradation of battery characteristics. In addition, if the weight ratio of the first binder to the inorganic particles is less than 1:40, the heat resistance will be reduced due to the insufficient content of the binder for adhering the inorganic particles.
[0064] Based on 100 wt % of the heat-resistant layer, the content of the inorganic particles may be 80 wt % to 99 wt %, for example, 85 wt % to 99 wt %, 90 wt % to 99 wt %, or 95 wt % to 99 wt %. When the inorganic particles are included in this range, the inorganic particles can achieve high mechanical rigidity and high transmittance of the heat-resistant layer and the separator including it.
[0065] The heat-resistant layer may include other binders commonly used in the art in addition to the first binder, and may include organic particles in addition to the above-mentioned inorganic particles.
[0066] The thickness of the heat-resistant layer is not particularly limited, but based on the thickness of the heat-resistant layer formed on one surface of the porous substrate, it can be 5% to 45% by length, or 10% to 30% by length of the thickness of the porous substrate, and can be, for example, 0.1 μm to 5 μm, 0.5 μm to 4 μm, 0.5 μm to 3 μm, or 1 μm to 2 μm. In this case, the heat-resistant layer can achieve excellent heat resistance and adhesion without reducing the air permeability of the separator.
[0067] Adhesive layer
[0068] According to an embodiment, the adhesive layer includes a second adhesive and a third adhesive, the second adhesive includes a copolymer including a first unit derived from a vinyl aromatic monomer, a second unit derived from an alkyl acrylate, and a third unit derived from a phosphonate monomer, the third adhesive includes a fluorine-based polymer, and a weight ratio of the second adhesive to the third adhesive is 1:1 to 1:6.
[0069] The adhesive layer can maximize the adhesion between the separator and the electrode by including the second binder and the third binder in a weight ratio of 1:1 to 1:6, and the adhesion can be further increased after a certain period of time after the battery is manufactured (for example, after about 60 days), and both the high temperature cycle life characteristics and the high temperature storage characteristics of the battery can also be improved. When the amount of the third binder included in the adhesive layer is less than the amount of the second binder, the high temperature storage characteristics of the battery are rapidly deteriorated, and when the amount of the third binder exceeds 6 times the amount of the second binder, the adhesion between the separator and the electrode will be rapidly reduced after about 60 days after manufacturing.
[0070] Second binder
[0071] The copolymer including the aforementioned first to third units can exhibit excellent adhesion even at low temperature and low pressure, so it can be used in battery types to which high temperature and high pressure processes are difficult to apply, which is advantageous in the process, and even a very small amount can maximize the adhesion between the separator and the negative electrode, improve the heat resistance and adhesion of the separator, and at the same time, dramatically improve the high temperature cycle life characteristics and high temperature storage characteristics of the battery.
[0072] In the second binder, the first unit derived from the vinyl aromatic monomer can increase the adhesion of the adhesive layer and improve the dispersibility and processability of the adhesive layer composition. For example, the first unit can be represented by Chemical Formula 1.
[0073] [Chemical formula 1]
[0074]
[0075] In Chemical Formula 1, R1 is hydrogen, fluorine, substituted or unsubstituted C1 to C6 alkyl, or substituted or unsubstituted C6 to C20 aryl, L 1 is a substituted or unsubstituted C1 to C6 alkylene group, a substituted or unsubstituted C3 to C10 cycloalkylene group, a substituted or unsubstituted C6 to C20 arylene group, or a combination thereof, a is 0 or 1, * represents the portion of the carbon linked to the benzene ring, R 2 is fluorine, substituted or unsubstituted C1 to C6 alkyl, substituted or unsubstituted C6 to C20 aryl, or substituted or unsubstituted C1 to C6 alkenyl, and b is an integer of 0 to 5.
[0076] For example, in Formula 1, R 1 It can be hydrogen or methyl, R 2 can be fluorine, methyl or ethyl, and b can be 0 or 1.
[0077] The vinyl aromatic monomer may be, for example, styrene, α-methylstyrene, fluorostyrene, vinyltoluene, divinylbenzene, 1,1-diphenylethylene, or a combination thereof.
[0078] The second unit derived from an alkyl acrylate can help improve the adhesion of the adhesive layer and achieve appropriate air permeability and heat resistance. Here, the alkyl group can be an alkyl group having 1 to 20 carbon atoms (i.e., a C1 to C20 alkyl group), and the acrylate includes methacrylate and acrylate. For example, the second unit can be represented by Chemical Formula 2.
[0079] [Chemical formula 2]
[0080]
[0081] In chemical formula 2, R 3 is hydrogen, fluorine, substituted or unsubstituted C1 to C6 alkyl, or substituted or unsubstituted C6 to C20 aryl, and R 4 It is a C1 to C20 alkyl group.
[0082] In chemical formula 2, R 4 For example, it may be a C5 to C18 alkyl group, or a C6 to C15 alkyl group. In this case, the second binder can achieve appropriate air permeability and heat resistance, while exhibiting excellent adhesion under low temperature and low pressure conditions.
[0083] The third unit derived from the phosphonate monomer allows the second binder to achieve excellent adhesion under low temperature and low pressure conditions, and can help the second binder have an appropriate glass transition temperature and swelling degree, and even if a very small amount of the binder is used, excellent adhesion can be achieved and high heat resistance and air permeability can be achieved.
[0084] The phosphonate monomer refers to a monomer including a phosphonate group and a C=C double bond. The phosphonate group may be represented by -P(=O)(OR)(OR'), wherein R and R' are organic groups other than hydrogen. The third unit may be represented by Chemical Formula 3, for example.
[0085] [Chemical formula 3]
[0086]
[0087] In chemical formula 3, R 5 is hydrogen, fluorine, substituted or unsubstituted C1 to C6 alkyl, or substituted or unsubstituted C6 to C20 aryl, L 2 is a carboxyl group (—C(═O)O—), a carbonyl group (—C(═O)—), an ether group (—O—), a substituted or unsubstituted C1 to C6 alkylene group, a substituted or unsubstituted C3 to C10 cycloalkylene group, a substituted or unsubstituted C6 to C20 arylene group, or a combination thereof, c is 0 or 1, R 6 and R 7 are the same as or different from each other, and are each independently a substituted or unsubstituted C1 to C10 alkyl group, or a substituted or unsubstituted C6 to C20 aryl group.
[0088] As an example, in Chemical Formula 3, R 5 It can be hydrogen or methyl, L 2 can be a carboxyl group, a substituted or unsubstituted C1 to C6 alkylene group, or a combination thereof, and R 6 and R 7 May independently be a C1 to C6 alkyl group.
[0089] The phosphonate-based monomer may be, for example, acrylphosphonate, and in this case, the second binder may achieve excellent adhesion under low temperature and low pressure conditions even in a small amount and may exhibit excellent workability.
[0090] The third unit may be derived from, for example, an acrylphosphonate-based monomer, and may be represented by Chemical Formula 4.
[0091] [Chemical formula 4]
[0092]
[0093] In chemical formula 4, R 5 is hydrogen, fluorine, substituted or unsubstituted C1 to C6 alkyl, or substituted or unsubstituted C6 to C20 aryl, L 3 is a substituted or unsubstituted C1 to C6 alkylene group, R 6 and R 7are the same as or different from each other and are each independently a substituted or unsubstituted C1 to C10 alkyl group, or a substituted or unsubstituted C6 to C20 aryl group, and R 8 It is hydrogen or methyl.
[0094] As an example, the acrylphosphonate monomer may be dimethyl [(acryloxy) methyl] phosphonate, dimethyl [(acryloxy) ethyl] phosphonate, diethyl [(acryloxy) methyl] phosphonate, or diethyl [(acryloxy) ethyl] phosphonate, wherein the acryl group may be replaced by a methacryloyl group. If a third unit derived from such a monomer is included, the second binder may achieve excellent adhesion under low temperature and low pressure conditions even in a small amount, and may exhibit excellent processability.
[0095] In the second binder, the copolymer may include, for example, 40wt% to 80wt% of the first unit, 5wt% to 40wt% of the second unit, and 0.1wt% to 20wt% of the third unit. For example, the copolymer of the second binder may include 50wt% to 70wt% of the first unit, 10wt% to 30wt% of the second unit, and 5wt% to 20wt% of the third unit. The amount range of each unit is based on 100wt% of the copolymer. If each unit meets these amount ranges, the second binder can achieve excellent adhesion under low temperature and low pressure conditions even in a small amount without deteriorating the heat resistance and air permeability of the diaphragm, thereby improving processability, cycle life characteristics and safety.
[0096] The second binder can be in the form of particles, and can maintain the particle form without being dissolved in an aqueous solvent. In this case, the average particle size (D50) of the second binder can be 0.1 μm to 1 μm, for example, 0.2 μm to 0.9 μm, 0.2 μm to 0.8 μm or 0.2 μm to 0.7 μm. When this particle size range is met, the adhesive layer can achieve excellent low temperature and low pressure adhesion even at a thin thickness without deteriorating the heat resistance and air permeability of the diaphragm. Here, the average particle size can refer to the diameter (D50) of particles measured by a particle size analyzer and having a cumulative volume of 50% by volume in a particle size distribution.
[0097] For example, the second binding agent can be in the form of particles with core-shell structure, in which case, it is conducive to ensuring appropriate average particle diameter and swelling degree. When the second binding agent has core-shell structure, the shell can be made of a copolymer comprising the aforementioned first unit, the second unit and the third unit. The material of the core is not particularly limited, and can be, for example, acrylic polymer, diene polymer or their copolymer.
[0098] The glass transition temperature of the second binder may be 60° C. to 90° C., for example, 65° C. to 75° C. When the second binder has a glass transition temperature within this range, it is advantageous to achieve adhesion under low temperature and low pressure conditions, and even a small amount may exhibit excellent adhesion without deteriorating the characteristics of the separator.
[0099] The swelling degree of the second binder of the adhesive layer may be 600% to 1000%, for example, 700% to 900%. If the second binder has a swelling degree in this range, excellent adhesion can be maintained during the battery manufacturing process and operation, and the adhesion between the separator and the electrode can be improved. Here, the swelling degree may refer to the swelling degree after the second binder is left standing in the electrolyte at 60°C for 72 hours.
[0100] The third binder
[0101] The third binder in the adhesive layer includes a fluorine-based polymer and can be expressed as a fluorine-based binder. The third binder is used to maximize the adhesion between the separator and the electrode in the adhesive layer, while preventing the degradation of the high-temperature cycle life characteristics and high-temperature storage characteristics of the battery when stored for a long time at high temperature, such as capacity reduction or resistance increase.
[0102] The fluorine-based polymer may be, for example, a vinylidene fluoride-based polymer, and may specifically be a polyvinylidene fluoride homopolymer or a polyvinylidene fluoride copolymer. The fluorine-based polymer may be, for example, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene, polyvinylidene fluoride-tetrafluoroethylene, polyvinylidene fluoride-trifluoroethylene, polyvinylidene fluoride-chlorotrifluoroethylene, polyvinylidene fluoride-ethylene, or a combination thereof.
[0103] The weight average molecular weight (Mw) of the fluorine-based polymer can be 500,000 g / mol to 1,500,000 g / mol, for example, 1,000,000 g / mol to 1,500,000 g / mol. As an example, the fluorine-based polymer can be a mixture of two or more types with different weight average molecular weights, and can include, for example, one or more types with a weight average molecular weight less than or equal to 1,000,000 g / mol and one or more types with a weight average molecular weight greater than or equal to 1,000,000 g / mol. Fluorine-based polymers with this molecular weight range can maximize the adhesion between the separator and the negative electrode, effectively inhibit the shrinkage of the porous substrate at high temperatures, and improve the high temperature storage characteristics of the battery.
[0104] The third binder may be in the form of particles, and the size of the particles (i.e., average particle size (D50)) may be 50 nm to 1 μm, 50 nm to 500 nm, 100 nm to 500 nm, or 100 nm to 250 nm. If the average particle size of the third binder satisfies the above range, processability can be improved and the adhesion between the separator and the negative electrode can be maximized. The average particle size (D50) of the third binder can be measured using a particle size analyzer using laser diffraction.
[0105] In the adhesive layer, the second binder and the third binder are mixed in a weight ratio of 1: 1 to 1: 6 (e.g., 1: 2 to 1: 6, 1: 3 to 1: 6, 1: 3 to 1: 5), or can be mixed in a weight ratio of 1: 1 to 1: 3. If mixed in this ratio, both the high temperature cycle life characteristics and the high temperature storage characteristics of the battery can be improved while maximizing the adhesion of the adhesive layer.
[0106] The thickness of the adhesive layer is not particularly limited, but may be 1% to 15% by length, or 1% to 10% by length of the thickness of the porous substrate, and may be, for example, 0.05 μm to 3 μm, or 0.1 μm to 2 μm. The adhesive layer according to the embodiment has such a thin thickness that it does not deteriorate the performance of the separator, and may exhibit excellent adhesion despite the thin thickness.
[0107] In an embodiment, a method for manufacturing a separator for a rechargeable lithium battery is provided, the method comprising: preparing a porous substrate; coating a heat-resistant layer composition comprising a first binder, inorganic particles and a solvent on one surface of the porous substrate; and coating an adhesive layer composition comprising a second binder and a third binder and a solvent in a weight ratio of 1:1 to 1:6 on the other surface of the porous substrate, and then drying it.
[0108] At this time, the loading amount of the adhesive layer composition can be, for example, 0.05 g / m 2 Up to 0.2g / m 2 , or 0.1g / m 2 Up to 0.2g / m 2 In this case, the adhesive layer can achieve excellent adhesion without deteriorating the characteristics of the separator.
[0109] In the method for manufacturing the diaphragm, the solvent of the heat-resistant layer composition and the solvent of the adhesive layer composition can be an aqueous solvent, and can be independently selected from water, an alcohol solvent and a combination thereof. The alcohol solvent can be, for example, methanol, ethanol, propanol, butanol or a combination thereof. These aqueous solvents are harmless to the body and have excellent drying properties, so that mass production can be achieved without reducing productivity.
[0110] The diaphragm according to the embodiment can achieve ultra-high heat resistance. For example, the dry shrinkage rate of the diaphragm can be less than or equal to 5%, and the dry shrinkage rates in the horizontal direction and the vertical direction can be less than or equal to 4%, or less than or equal to 3%. Here, the dry shrinkage rate refers to the degree of shrinkage of the diaphragm after standing for 1 hour at 150°C.
[0111] In addition, the separator according to the embodiment can achieve excellent adhesion with the electrode at the interface. For example, the wet adhesion of the separator may be greater than or equal to 0.10 gf / mm, greater than or equal to 0.15 gf / mm, or greater than or equal to 0.20 gf / mm. Here, the wet adhesion may refer to the peeling force between the separator and the electrode measured after the electrolyte is injected into the battery case and left to stand for 2 hours at 40°C and 50 kg.
[0112] In the separator, the heat-resistant layer and the adhesive layer may each independently have a single-layer structure or a multilayer structure. In the multilayer structure, layers selected from organic layers, inorganic layers, and organic / inorganic layers may be arbitrarily arranged. The multilayer structure may be a two-layer structure, a three-layer structure, or a four-layer structure, but is not necessarily limited to these structures, and may be selected according to the desired composite separator properties.
[0113] Rechargeable lithium battery
[0114] In an embodiment, a rechargeable lithium battery includes a positive electrode, a negative electrode, the above-mentioned separator between the positive electrode and the negative electrode, and an electrolyte.
[0115] Figure 1 is a schematic diagram showing a rechargeable lithium battery according to an embodiment. Figure 1 According to an embodiment, a rechargeable lithium battery 100 includes a battery cell, a battery case 120 accommodating the battery cell, and a sealing member 140 sealing the battery case 120, the battery cell including a positive electrode 114, a negative electrode 112 facing the positive electrode 114, a separator 113 between the positive electrode 114 and the negative electrode 112, and an electrolyte impregnating the positive electrode 114, the negative electrode 112 and the separator 113.
[0116] Positive electrode
[0117] The positive electrode 114 includes a current collector and a positive electrode active material layer on the current collector, and the positive electrode active material layer includes a positive electrode active material and may optionally include a binder and / or a conductive material. Here, the current collector may be, for example, aluminum foil, but is not limited thereto.
[0118] The positive electrode active material may include a lithiated intercalation compound that reversibly intercalates and deintercalates lithium ions. Examples of the positive electrode active material include a compound represented by any one of the following chemical formulas:
[0119] Li a A 1-b X b D2(0.90≤a≤1.8,0≤b≤0.5);
[0120] Li a A 1-b X b O 2-c D c (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05);
[0121] Li a HAVE BEEN 1-b X b O 2-c D c (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05);
[0122] Li a HAVE BEEN 2-b X b O 4-c D c (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05);
[0123] Li a Ni 1-b-c Co b X c D α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α≤2);
[0124] Li a Ni 1-b-c Co b X c O 2-α T α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0<α<2);
[0125] Li a Ni 1-b-c Co b X c O 2-α T2(0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0<α<2);
[0126] Li a Ni 1-b-c Mr b X c D α(0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0<α≤2);
[0127] Li a Ni 1-b-c Mr b X c O 2-α T α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0<α<2);
[0128] Li a Ni 1-b-c Mr b X c O 2-α T2(0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0<α<2);
[0129] Li a Ni b HAVE BEEN c G d O2(0.90≤a≤1.8,0≤b≤0.9,0≤c≤0.5,0.001≤d≤0.1);
[0130] Li a Ni b Co c Mr d G e O2(0.90≤a≤1.8,0≤b≤0.9,0≤c≤0.5,0≤d≤0.5,0.001≤e
[0131] ≤0.1);
[0132] Li a NiG b O2(0.90≤a≤1.8,0.001≤b≤0.1);
[0133] Li a CoG b O2(0.90≤a≤1.8,0.001≤b≤0.1);
[0134] Li a Mr 1-b G b O2(0.90≤a≤1.8,0.001≤b≤0.1);
[0135] Li a Mn2G b O4(0.90≤a≤1.8,0.001≤b≤0.1);
[0136] Li a Mn 1-g G g PO4(0.90≤a≤1.8, 0≤g≤0.5);
[0137] QO2; QS2; LiQS2;
[0138] V2O5; LiV2O5;
[0139] LiZO2;
[0140] LiNiVO4;
[0141] Li (3-f) J2(PO4)3(0≤f≤2);
[0142] Li (3-f) Fe2(PO4)3(0≤f≤2);
[0143] Li a FePO4(0.90≤a≤1.8).
[0144] In the above chemical formula, A is selected from Ni, Co, Mn and combinations thereof; X is selected from Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, rare earth elements and combinations thereof; D is selected from O, F, S, P and combinations thereof; E is selected from Co, Mn and combinations thereof; T is selected from F, S, P and combinations thereof; G is selected from Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V and combinations thereof; Q is selected from Ti, Mo, Mn and combinations thereof; Z is selected from Cr, V, Fe, Sc, Y and combinations thereof; and J is selected from V, Cr, Mn, Co, Ni, Cu and combinations thereof.
[0145] The positive electrode active material can be a lithium-metal composite oxide, for example, lithium cobalt oxide (LCO), lithium nickel oxide (LNO), lithium nickel cobalt oxide (LNCO), lithium nickel cobalt aluminum oxide (LNCAO), lithium nickel cobalt manganese oxide (LNCMO), lithium manganese oxide (LMO), or lithium iron phosphate (LFP).
[0146] A compound having a coating layer on the surface can be used, or a mixture of the above-mentioned compound and a compound having a coating layer can be used. The coating layer may include at least one coating element compound selected from an oxide of a coating element, a hydroxide of a coating element, an oxyhydroxide of a coating element, an oxycarbonate of a coating element, and a hydroxycarbonate of a coating element. The compound forming the coating layer may be amorphous or crystalline. The coating element included in the coating layer may include Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a combination thereof. As an example, the coating layer may include lithium zirconium oxide, for example, Li2O-ZrO2. The coating layer formation process may use a method that does not adversely affect the physical properties of the positive electrode active material, such as a spraying method, an impregnation method, and the like.
[0147] The positive electrode active material may include, for example, one or more types of lithium-metal composite oxides represented by Chemical Formula 11.
[0148] [Chemical formula 11]
[0149] Li a M 11 1-y11-z11 M 12 y11 M 13 z11 O2
[0150] In Chemical Formula 11, 0.9≤a≤1.8, 0≤y11≤1, 0≤z11≤1, 0≤y11+z11<1, and M 11 、M 12 and M 13 Independently any one selected from elements such as Ni, Co, Mn, Al, Mg, Ti or Fe, and combinations thereof.
[0151] For example, M 11 It can be Ni, and M 12 and M 13 Mn, Al, Mg, Ti or Fe may be independently a metal, such as Co, Mn, Al, Mg, Ti or Fe. 11 Can be Ni, M 12 It can be Co, M 13 It may be Mn or Al, but is not limited thereto.
[0152] In an embodiment, the positive electrode active material may include a lithium nickel-based composite oxide represented by Chemical Formula 12.
[0153] [Chemical formula 12]
[0154] Li a12 Ni x12 M14 y12 M 15 1-x12-y12 O2
[0155] In Chemical Formula 12, 0.9 ≤ a12 ≤ 1.8, 0.3 ≤ x12 ≤ 1, 0 ≤ y12 ≤ 0.7, and M 14 and M 15 are each independently at least one element selected from Al, B, Ba, Ca, Ce, Co, Cr, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, and Zr.
[0156] In Chemical Formula 12, 0.3 ≤ x12 ≤ 0.99 and 0.01 ≤ y12 ≤ 0.7, 0.4 ≤ x12 ≤ 0.99 and 0.01 ≤ y12 ≤ 0.6, 0.5 ≤ x12 ≤ 0.99 and 0.01 ≤ y12 ≤ 0.5, 0.6 ≤ x12 ≤ 0.99 and 0.01 ≤ y12 ≤ 0.4, 0.7 ≤ x12 ≤ 0.99 and 0.01 ≤ y12 ≤ 0.3, 0.8 ≤ x12 ≤ 0.99 and 0.01 ≤ y12 ≤ 0.2, or 0.9 ≤ x12 ≤ 0.99 and 0.01 ≤ y12 ≤ 0.1.
[0157] For example, the positive electrode active material may include a lithium nickel cobalt-based oxide represented by Chemical Formula 13.
[0158] [Chemical Formula 13]
[0159] Li a13 Ni x13 Co y13 M 16 1-x13-y13 O2
[0160] In Chemical Formula 13, 0.9 ≤ a13 ≤ 1.8, 0.3 ≤ x13 < 1, 0 < y13 ≤ 0.7, and M 16 is at least one element selected from Al, B, Ba, Ca, Ce, Cr, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, and Zr.
[0161] In Chemical Formula 13, 0.3 ≤ x13 ≤ 0.99 and 0.01 ≤ y13 ≤ 0.7, 0.4 ≤ x13 ≤ 0.99 and 0.01 ≤ y13 ≤ 0.6, 0.5 ≤ x13 ≤ 0.99 and 0.01 ≤ y13 ≤ 0.5, 0.6 ≤ x13 ≤ 0.99 and 0.01 ≤ y13 ≤ 0.4, 0.7 ≤ x13 ≤ 0.99 and 0.01 ≤ y13 ≤ 0.3, 0.8 ≤ x13 ≤ 0.99 and 0.01 ≤ y13 ≤ 0.2, or 0.9 ≤ x13 ≤ 0.99 and 0.01 ≤ y13 ≤ 0.1.
[0162] Based on the total amount of metal other than lithium, the nickel content in the lithium-nickel composite oxide can be greater than or equal to 30 mol%, for example, greater than or equal to 40 mol%, greater than or equal to 50 mol%, greater than or equal to 60 mol%, greater than or equal to 70 mol%, greater than or equal to 80 mol% or greater than or equal to 90 mol%, and can be less than or equal to 99.9 mol% or less than or equal to 99 mol%.
[0163] As an example, a lithium-nickel composite oxide may be a high-nickel oxide including nickel greater than or equal to 90 mol% based on the total amount of metals other than lithium. In this case, there is an advantage of achieving high capacity and high output characteristics, but there is a problem of generating a large amount of gas during battery operation. At this time, the generated gas is located at the interface between the electrode and the diaphragm, causing the precipitation of lithium salts, which can cause a sharp drop in capacity or short circuit and fire. In order to solve this problem, when the diaphragm according to the embodiment is applied, the heat resistance is improved and the adhesion between the diaphragm and the electrode is enhanced, thereby effectively suppressing the precipitation of lithium salts, thereby effectively improving the safety and cycle life characteristics of the battery.
[0164] When a positive electrode using a high-nickel positive electrode active material is combined with a separator according to an embodiment and a battery type that is difficult to apply high temperature and high pressure processes to is applied, the effect of the embodiment can be maximized, that is, the effect of improving the heat resistance, safety, processability, high temperature cycle life characteristics and high temperature storage characteristics of the battery.
[0165] The average particle size (D50) of the positive electrode active material may be 1 μm to 25 μm, for example, 4 μm to 25 μm, 5 μm to 20 μm, 8 μm to 20 μm, or 10 μm to 18 μm. The positive electrode active material having a particle size within the range may be coordinated and mixed with other components in the positive electrode active material layer and achieve high capacity and high energy density. The average particle size may refer to the diameter (D50) of particles having a cumulative volume of 50% by volume in the particle size distribution as measured by a particle size analyzer.
[0166] The positive electrode active material may be in the form of secondary particles formed by agglomeration of a plurality of primary particles or in the form of a single particle. In addition, the positive electrode active material may have a spherical shape, a shape close to a spherical shape, a polyhedral shape, or an irregular shape.
[0167] The content of the positive electrode active material may be 55 wt % to 99.8 wt %, for example, 80 wt % to 90 wt %, based on the total weight of the positive electrode active material layer. Within the above range, the capacity of the rechargeable lithium battery may be maximized and cycle-life characteristics may be improved.
[0168] The binder improves the bonding properties between the positive electrode active material particles and between the positive electrode active material particles and the current collector. Examples thereof may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc., but are not limited thereto.
[0169] The amount of the binder in the positive electrode active material layer may be 1 wt % to 5 wt % based on the total weight of the positive electrode active material layer.
[0170] A conductive material is included to provide electrode conductivity, and any conductive material can be used as the conductive material unless it causes a chemical change. Examples of the conductive material include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof. The amount of the conductive material in the positive electrode active material layer may be 1 wt% to 5 wt% based on the total weight of the positive electrode active material layer.
[0171] Negative electrode
[0172] A negative electrode for a rechargeable lithium battery includes a current collector and a negative electrode active material layer positioned on the current collector. The negative electrode active material layer includes a negative electrode active material and may further include a binder and / or a conductive material.
[0173] The negative electrode active material may include a material that reversibly intercalates / deintercalates lithium ions, lithium metal, a lithium metal alloy, a material capable of doping / dedoping lithium, or a transition metal oxide.
[0174] The material that reversibly intercalates / deintercalates lithium ions may include, for example, crystalline carbon, amorphous carbon, or a combination thereof as a carbonaceous negative electrode active material. Crystalline carbon may be natural graphite or artificial graphite in the form of non-shaped or flake, flaky, spherical, or fibrous shapes. Amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonization product, calcined coke, etc.
[0175] Lithium metal alloys include alloys of lithium and a metal selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.
[0176] The materials capable of doping / dedoping lithium can be Si-based negative electrode active materials or Sn-based negative electrode active materials. The Si-based negative electrode active materials can include silicon, silicon-carbon composites, SiO x (0 < x < 2), Si-Q alloys (where Q is an alkali metal, alkaline earth metal, group 13 element, group 14 element, group 15 element, group 16 element, transition metal, rare earth element, and combinations thereof, but not Si), and the Sn-based negative electrode active materials can include Sn, SnO2, Sn-R alloys (where R is an alkali metal, alkaline earth metal, group 13 element, group 14 element, group 15 element, group 16 element, transition metal, rare earth element, and combinations thereof, but not Sn). At least one of these materials can be mixed with SiO2. The elements Q and R can be selected from Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.
[0177] The silicon-carbon composite can be, for example, a silicon-carbon composite including a core containing crystalline carbon and silicon particles and an amorphous carbon coating layer provided on the surface of the core. The crystalline carbon can be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon precursor can be coal tar pitch, mesophase pitch, petroleum pitch, coal oil, petroleum heavy oil, or a polymer resin (such as phenolic resin, furan resin, or polyimide resin). In this case, based on the total weight of the silicon-carbon composite, the content of silicon can be 10 wt% to 50 wt%. Additionally, based on the total weight of the silicon-carbon composite, the content of crystalline carbon can be 10 wt% to 70 wt%, and based on the total weight of the silicon-carbon composite, the content of amorphous carbon can be 20 wt% to 40 wt%. Additionally, the thickness of the amorphous carbon coating layer can be 5 nm to 100 nm. The average particle size (D50) of the silicon particles can be 10 nm to 20 μm. The average particle size (D50) of the silicon particles can be preferably 10 nm to 200 nm. The silicon particles can exist in an oxidized form, and in this case, the atomic content ratio of Si:O in the silicon particles indicating the degree of oxidation can be 99:1 to 33:67. The silicon particles can be SiO x particles, and in this case, the range of x in SiO x can be greater than 0 and less than 2.
[0178] The Si-based negative electrode active material or the Sn-based negative electrode active material may be mixed with the carbon-based negative electrode active material. When the Si-based negative electrode active material or the Sn-based negative electrode active material is mixed with the carbon-based negative electrode active material, the mixing ratio may be 1:99 to 90:10 by weight.
[0179] In the negative electrode active material layer, the negative electrode active material may be included in an amount of 95 wt % to 99 wt % based on the total weight of the negative electrode active material layer.
[0180] In an embodiment, the negative electrode active material layer further includes a binder and optionally may further include a conductive material. Based on the total weight of the negative electrode active material layer, the amount of the binder in the negative electrode active material layer may be 1wt% to 5wt%. In addition, when a conductive material is further included, the negative electrode active material layer may include 90wt% to 98wt% of the negative electrode active material, 1wt% to 5wt% of the binder and 1wt% to 5wt% of the conductive material.
[0181] The binder is used to adhere the negative electrode active material particles to each other well, and also to adhere the negative electrode active material to the current collector. The binder may be a non-water-soluble binder, a water-soluble binder, or a combination thereof.
[0182] The non-water-soluble binder may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, ethylene propylene copolymers, polystyrene, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.
[0183] The water-soluble binder can include a rubber binder or a polymer resin binder. The rubber binder can be selected from styrene-butadiene rubber, acrylated styrene-butadiene rubber, acrylonitrile-butadiene rubber, acrylic rubber, butyl rubber, fluororubber and combinations thereof. The polymer resin binder can be selected from polyethylene oxide, polyvinyl pyrrolidone, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, ethylene propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol and combinations thereof.
[0184] When a water-soluble binder is used as a negative electrode binder, a cellulose compound capable of imparting viscosity may be further included. As a cellulose compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose and their alkali metal salts may be mixed and used. The alkali metal may be Na, K or Li. Based on 100 parts by weight of the negative electrode active material, the amount of such a thickener may be 0.1 parts by weight to 3 parts by weight.
[0185] A conductive material is included to provide electrode conductivity, and any conductive material can be used as the conductive material unless it causes a chemical change. Examples of the conductive material include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powder or metal fiber of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0186] The current collector of the negative electrode may include one selected from the group consisting of copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.
[0187] Electrolyte
[0188] The electrolyte includes a non-aqueous organic solvent and a lithium salt.
[0189] The non-aqueous organic solvent is used as a medium for transmitting ions participating in the electrochemical reaction of the battery. The non-aqueous organic solvent can be a carbonate solvent, an ester solvent, an ether solvent, a ketone solvent or an alcohol solvent, or an aprotic solvent. Examples of carbonate solvents include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Examples of ester solvents include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, decanolactone, valerolactone, mevalonolactone, caprolactone, etc. Ether solvents can be dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, etc., and ketone solvents can be cyclohexanone, etc. In addition, the alcohol solvent can be ethanol, isopropanol, etc., and the aprotic solvent can be: nitrile, such as R-CN (wherein R is a C2 to C20 straight chain, branched or cyclic hydrocarbon group, and can include a double bond, an aromatic ring or an ether bond); amide, such as dimethylformamide; dioxolane, such as 1,3-dioxolane; cyclopentane; etc.
[0190] The nonaqueous organic solvent may be used alone or in a mixture, and when the organic solvent is used in a mixture, the mixing ratio may be controlled according to desired battery performance.
[0191] In addition, in the case of carbonate solvents, a mixture of cyclic carbonate and chain carbonate can be used. In this case, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9, the electrolyte can show excellent performance.
[0192] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent in addition to the carbonate-based solvent. In this case, the carbonate-based solvent and the aromatic hydrocarbon organic solvent may be mixed in a volume ratio of about 1:1 to about 30:1.
[0193] As the aromatic hydrocarbon solvent, an aromatic hydrocarbon compound represented by Chemical Formula I may be used.
[0194] [Chemical Formula I]
[0195]
[0196] In Formula I, R 4 To R 9 are the same or different and are selected from the group consisting of hydrogen, halogen, C1 to C10 alkyl, C1 to C10 haloalkyl, and combinations thereof.
[0197] Specific examples of aromatic hydrocarbon solvents may be selected from benzene, fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, chlorobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, iodobenzene, 1,2-diiodobenzene, 1,3-diiodobenzene, 1,4-diiodobenzene, 1,2,3-triiodobenzene, 1,2,4-triiodobenzene, toluene, fluorotoluene, , 2,3-difluorotoluene, 2,4-difluorotoluene, 2,5-difluorotoluene, 2,3,4-trifluorotoluene, 2,3,5-trifluorotoluene, chlorotoluene, 2,3-dichlorotoluene, 2,4-dichlorotoluene, 2,5-dichlorotoluene, 2,3,4-trichlorotoluene, 2,3,5-trichlorotoluene, iodotoluene, 2,3-diiodotoluene, 2,4-diiodotoluene, 2,5-diiodotoluene, 2,3,4-triiodotoluene, 2,3,5-triiodotoluene, xylene and combinations thereof.
[0198] The electrolyte may further include vinylene carbonate or ethylene carbonate compounds of Chemical Formula II to improve the cycle life of the battery.
[0199] [Chemical Formula II]
[0200]
[0201] In Chemical Formula II, R 10 and R 11 are the same or different and are selected from hydrogen, halogen, cyano, nitro and fluorinated C1 to C5 alkyl, provided that R 10 and R 11 At least one of them is selected from halogen, cyano, nitro and fluorinated C1 to C5 alkyl, but R 10 and R 11 Both are not hydrogen.
[0202] Examples of ethylene carbonate compounds may include difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, or fluoroethylene carbonate. The amount of the additive for improving the cycle life may be used within an appropriate range.
[0203] The lithium salt dissolved in the nonaqueous organic solvent supplies lithium ions in the battery, enables basic operation of the rechargeable lithium battery, and improves the transport of lithium ions between the positive electrode and the negative electrode.
[0204] Examples of lithium salts include those selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiN(SO2C2F5)2, Li(CF3SO2)2N, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (wherein x and y are natural numbers, for example, integers from 1 to 20), at least one of lithium difluoro(bis(oxalato)phosphate, LiCl, LiI, LiB(C2O4)2 (lithium bis(oxalato)borate; LiBOB) and lithium difluoro(oxalato)borate (LiDFOB).
[0205] The lithium salt may be used in a concentration range of 0.1 M to 2.0 M. If the lithium salt is included in the above concentration range, the electrolyte may have excellent performance and lithium ion mobility due to optimal electrolyte conductivity and viscosity.
[0206] Rechargeable lithium batteries can be classified as lithium ion batteries, lithium ion polymer batteries, and lithium polymer batteries, depending on the type of separator present and the electrolyte used in the battery. Rechargeable lithium batteries can have a variety of shapes and sizes, and include cylindrical, prismatic, coin, or pouch-type batteries, and can be thin film batteries or can be quite bulky in size. The structure and manufacturing methods of lithium ion batteries pertaining to the present disclosure are well known in the art.
[0207] Because the rechargeable lithium battery according to the embodiment achieves high capacity and has excellent storage stability, cycle life characteristics, and high rate characteristics at high temperatures, it can be used in electric vehicles (EVs), hybrid electric vehicles (such as plug-in hybrid electric vehicles (PHEVs)), and portable electronic devices.
[0208] Hereinafter, examples and comparative examples of the present invention are described. However, it will be understood that the examples are for illustrative purposes and are not to be construed as limiting the present invention.
[0209] Example 1
[0210] 1. Manufacturing of diaphragm
[0211] (1) Preparation of the first binder for the heat-resistant layer
[0212] Distilled water (6361g), acrylic acid (72.06g, 1.0mol), acrylamide (604.1g, 8.5mol), potassium persulfate (2.7g, 0.01mol), 2-acrylamide-2-methylpropanesulfonic acid (103.6g, 0.5mol) and 5N lithium hydroxide aqueous solution (based on the total amount of 2-acrylamide-2-methylpropanesulfonic acid is 1.05 equivalents) are placed in a 10L four-necked flask equipped with a stirrer, a thermometer and a condenser, and the internal pressure of the flask is reduced to 10mmHg with a diaphragm pump, then, restored to normal pressure with nitrogen, repeated three times. The reaction solution is controlled to be stable between 65°C and 70°C for 12 hours. The reaction solution is cooled to room temperature and the pH of the reaction solution is adjusted in the range of 7 to 8 by using 25% ammonia solution. In this manner, poly(acrylamide-co-2-acrylamide-2-methylpropanesulfonic acid-co-acrylic acid) lithium salt was prepared with acrylamide, 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid in a molar ratio of 85:5:10 to prepare a first binder.
[0213] (2) Formation of heat-resistant layer
[0214] The heat-resistant layer composition was prepared by mixing the prepared first binder and inorganic particles (boehmite, D50 = 0.3 μm) in an aqueous solvent at a weight ratio of 1:30. The prepared heat-resistant layer composition was coated on both surfaces of an 8 μm thick polyethylene porous substrate (SK Company, air permeability: 120 sec / 100 cc, puncture strength: 480 kgf) by bar coating so that each surface had a thickness of 1.5 μm, and dried.
[0215] (3) Formation of Adhesive Layer
[0216] A second binder having a core-shell structure, an average particle size (D50) of 0.5 μm, a glass transition temperature of 65° C., and a swelling degree of 800% was prepared. In the second binder, the core includes a copolymer of an alkyl acrylate and divinylbenzene, and the shell includes a copolymer of 70 wt % styrene, 20 wt % 2-ethylhexyl methacrylate, and 10 wt % acryl phosphonate. Preparation of polyvinylidene fluoride ( XPH-838, Solvay) was used as the third binder. The adhesive layer composition was prepared by mixing the second binder and the third binder in a water solvent at a weight ratio of 1:1.
[0217] The adhesive layer composition was coated on both surfaces of the heat-resistant layer using a bar coating method so as to have a thickness of 0.5 μm on each surface, and then dried.
[0218] Thus, a coated separator having a total thickness of about 12 μm was produced.
[0219] Figure 2 is a scanning electron microscope photograph of the surface of the separator adhesive layer of Example 1. Figure 2 In the embodiment, second binder particles having a particle size of approximately 0.5 μm to 0.6 μm and third binder particles having a particle size of approximately 0.1 μm to 0.2 μm can be confirmed.
[0220] 2. Manufacturing of battery cells
[0221] 96wt% LiNi 0.91 Co 0.05 Al 0.04 An O2 positive electrode active material, 2 wt% of a polyvinylidene fluoride binder, 2 wt% of a carbon nanotube conductive material and an N-methylpyrrolidone solvent were mixed with a mixer to prepare a positive electrode active material layer composition, and the positive electrode active material layer composition was coated on an aluminum foil, and then dried and rolled to manufacture a positive electrode.
[0222] 97 wt % of graphite, 1.5 wt % of styrene butadiene rubber binder, 1.5 wt % of carboxymethyl cellulose and distilled water solvent were mixed to prepare a negative electrode active material layer composition, and the negative electrode active material layer composition was coated on a copper current collector, then dried and pressed to manufacture a negative electrode.
[0223] A rechargeable lithium battery cell was fabricated by placing the prepared coated separator between a positive electrode and a negative electrode, inserting it into a prismatic case, and injecting an electrolyte solution, which was a solution of 1.1 M LiPF6 dissolved in a solvent mixed with ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:5.
[0224] Example 2
[0225] A separator and a battery cell were manufactured in the same manner as in Example 1, except that the second binder and the third binder were mixed at a weight ratio of 1:2 in the adhesive layer of the separator.
[0226] Example 3
[0227] A separator and a battery cell were manufactured in the same manner as in Example 1, except that the second binder and the third binder were mixed at a weight ratio of 1:3 in the adhesive layer of the separator.
[0228] Example 4
[0229] A separator and a battery cell were manufactured in the same manner as in Example 1, except that the second binder and the third binder were mixed at a weight ratio of 1:4 in the adhesive layer of the separator.
[0230] Example 5
[0231] A separator and a battery cell were manufactured in the same manner as in Example 1, except that the second binder and the third binder were mixed at a weight ratio of 1:5 in the adhesive layer of the separator.
[0232] Example 6
[0233] A separator and a battery cell were manufactured in the same manner as in Example 1, except that the second binder and the third binder were mixed at a weight ratio of 1:6 in the adhesive layer of the separator.
[0234] Comparative Example 1
[0235] A separator and a battery cell were manufactured in the same manner as in Example 1, except that only the third binder was used in the adhesive layer of the separator without using the second binder.
[0236] Comparative Example 2
[0237] A separator and a battery cell were manufactured in the same manner as in Example 1, except that only the second binder was used without using the third binder in the adhesive layer of the separator.
[0238] Comparison Example 3
[0239] A separator and a battery cell were manufactured in the same manner as in Example 1, except that the second binder and the third binder were mixed at a weight ratio of 1:0.5 in the adhesive layer of the separator.
[0240] Comparison Example 4
[0241] A separator and a battery cell were manufactured in the same manner as in Example 1, except that the second binder and the third binder were mixed at a weight ratio of 1:7 in the adhesive layer of the separator.
[0242] Comparative Example 5
[0243] A separator and a battery cell were manufactured in the same manner as in Example 1, except that a binder having a core-shell structure in which the shell was made of styrene-co-2-ethylhexyl methacrylate-co-acrylonitrile copolymer and having a glass transition temperature of 65° C. and a swelling degree of 800% was used as the second binder of the adhesive layer.
[0244] Comparative Example 6
[0245] A separator and a battery cell were manufactured in the same manner as in Example 1, except that a binder having a core-shell structure in which the shell was made of styrene-co-butyl acrylate-co-acrylonitrile copolymer and having a glass transition temperature of 55° C. and a swelling degree of 400% was used as the second binder of the adhesive layer.
[0246] Evaluation Example 1: Evaluation of Dry Shrinkage of Separator
[0247] The coated separators prepared in the examples and comparative examples were cut into a size of (8 cm) × (8 cm) and placed in a convection oven at 150° C. for 1 hour, and then the length change rates of the coated separators in the machine direction (MD) and the transverse direction (TD) were calculated. The results are shown in Table 1.
[0248] Evaluation Example 2: Evaluation of wet adhesion of separator
[0249] The battery cells manufactured in the examples and comparative examples were kept at a temperature of 40°C and a load of 50kg for 2 hours, and then subjected to a peeling test (0 days), and then, after 60 days, the peeling test was performed again (60 days). After the separator was separated from the positive electrode by about 15mm, and then the positive electrode was fixed to the lower clamp and the separator was fixed to the upper clamp, the two clamps were pulled apart in a 180° direction, and the positive electrode and the separator were peeled off at 100mm / min. The force required to peel off 40mm was measured three times and the arithmetic mean was obtained. The peeling test for the separator and the negative electrode was also performed in the same manner, and the results are shown in Table 1.
[0250] Evaluation Example 3: Evaluation of high temperature cycle life characteristics and high temperature storage characteristics of battery cells
[0251] The battery cells of the examples and comparative examples were charged at 55°C at a constant current of 0.1C to an upper voltage of 4.25V, and then discharged at a constant current of 0.1C until a cut-off discharge voltage of 3.5V to perform initial charge and discharge. Then, charging at 0.5C and discharging at 0.5C were repeated 10 times in a voltage range of 3.5V to 4.25V. The battery temperature was measured after 10 cycles, and the degree of increase compared to the initial temperature was measured and shown in Table 1. In addition, the ratio of the discharge capacity in the 10th cycle to the initial discharge capacity was calculated and shown in Table 1 as efficiency.
[0252] In addition, the battery cells of the examples and comparative examples that were initially charged and discharged were stored at 60°C for 90 days, and then one cycle was performed to measure the ratio of the discharge capacity after the cycle to the initial discharge capacity (ie, the capacity retention rate) to evaluate the high temperature storage characteristics. The results are shown in Table 1.
[0253] (Table 1)
[0254]
[0255] Referring to Table 1, Comparative Example 1 using only the third binder in the adhesive layer of the separator showed that the wet adhesion between the separator and the negative electrode was very low, the temperature change in the high-temperature cycle life characteristics was large, and the efficiency was significantly low (81%). Comparative Example 2 in which only the second binder was applied to the adhesive layer of the separator showed that in the evaluation of the high-temperature storage characteristics, the capacity retention rate was reduced to 80%.
[0256] Comparative Example 3 using the second binder and the third binder at a weight ratio of 1:0.5 in the adhesive layer of the separator shows that in the evaluation of high temperature storage characteristics, the capacity retention rate is reduced to 85%. Comparative Example 4 in which the weight ratio of the second binder to the third binder is changed to 1:7 shows that the wet adhesion between the separator and the negative electrode is significantly lower, at the level of 0.08 gf / mm (0 day) and 0.13 gf / mm (60 days), and the temperature change is slightly larger in the high temperature cycle life characteristics.
[0257] In Comparative Examples 5 and 6 in which the composition of the second binder of the diaphragm bonding layer was changed, both the diaphragm-positive electrode and diaphragm-negative electrode adhesion forces were significantly lower, the temperature change was large and the efficiency was low in the evaluation of the high-temperature cycle life characteristics, and in Comparative Example 6, the capacity retention rate was significantly reduced to 75% in the evaluation of the high-temperature storage characteristics.
[0258] On the other hand, in Examples 1 to 6, the dry shrinkage of the separator is less than 2.3%, showing excellent heat resistance, and the wet adhesion of the separator-positive electrode and the separator-negative electrode is very high, being more than or equal to 0.18 gf / mm. In addition, in the evaluation of the high-temperature cycle life characteristics, the temperature change is small, being less than or equal to 6.8°C, and the efficiency is more than 89%, thereby evaluating that the high-temperature cycle life characteristics are improved. In addition, in the evaluation of the high-temperature storage characteristics, the analysis capacity retention rate is more than 89%, showing that the high-temperature storage characteristics are improved.
[0259] Although the preferred embodiment has been described in detail above, the scope of the present invention is not limited thereto. In addition, various modifications and improvements made by those skilled in the art using the basic concept defined in the claims should also be understood to fall within the scope of the present invention.
[0260] [Explanation of Reference Numerals]
[0261] 100: Rechargeable lithium battery 112: Negative electrode
[0262] 113: separator 114: positive electrode
[0263] 120: battery case 140: sealing member.
Claims
1. A separator for a rechargeable lithium battery, the separator for a rechargeable lithium battery comprising: Porous substrate, a heat-resistant layer on at least one surface of the porous substrate; as well as an adhesive layer, on the heat-resistant layer, Wherein, the heat-resistant layer comprises a first binder and inorganic particles, The first binder comprises polyacrylate, polyacrylic acid, polyacrylonitrile, polyvinyl alcohol, polysulfonic acid, polyacrylamide, polyamide, polyurea, polyurethane, copolymers thereof or combinations thereof, The adhesive layer includes a second adhesive and a third adhesive, The second binder includes a copolymer including a first unit derived from a vinyl aromatic monomer, a second unit derived from an alkyl acrylate, and a third unit derived from a phosphonate monomer, The third binder includes a fluorine-based polymer, and A weight ratio of the second binder to the third binder in the adhesive layer is 1:1 to 1:
6.
2. The separator for a rechargeable lithium battery according to claim 1, wherein In the heat-resistant layer, the first binder includes a copolymer, which includes a first unit derived from (meth)acrylamide, a second unit derived from a monomer containing a sulfonic acid group, and a third unit derived from (meth)acrylic acid, (meth)acrylate, a monomer containing a nitrile group, a monomer containing an alcohol group, or a combination thereof.
3. The separator for a rechargeable lithium battery according to claim 2, wherein: In the first binder of the heat-resistant layer, the copolymer includes 55 mol % to 99 mol % of the first unit, 0.5 mol % to 40 mol % of the second unit, and 0.5 mol % to 40 mol % of the third unit.
4. The separator for a rechargeable lithium battery according to claim 1, wherein In the heat-resistant layer, a weight ratio of the first binder to the inorganic particles is 1:20 to 1:
40.
5. The separator for a rechargeable lithium battery according to claim 1, wherein The average particle size D50 of the inorganic particles is 0.1 μm to 2 μm.
6. The separator for a rechargeable lithium battery according to claim 1, wherein The thickness of the heat-resistant layer is 0.1 μm to 5 μm.
7. The separator for a rechargeable lithium battery according to claim 1, wherein The first unit in the second binder of the adhesive layer is represented by Chemical Formula 1: [Chemical formula 1] Wherein, in Chemical Formula 1, R 1 is hydrogen, fluorine, substituted or unsubstituted C1 to C6 alkyl, or substituted or unsubstituted C6 to C20 aryl, L 1 is a substituted or unsubstituted C1 to C6 alkylene group, a substituted or unsubstituted C3 to C10 cycloalkylene group, a substituted or unsubstituted C6 to C20 arylene group, or a combination thereof, a is 0 or 1, * represents the portion of the carbon linked to the benzene ring, R 2 is fluorine, substituted or unsubstituted C1 to C6 alkyl, substituted or unsubstituted C6 to C20 aryl, or substituted or unsubstituted C1 to C6 alkenyl, and b is an integer of 0 to 5.
8. The separator for a rechargeable lithium battery according to claim 1, wherein In the first unit of the second binder of the adhesive layer, the vinyl aromatic monomer is styrene, α-methylstyrene, fluorostyrene, vinyltoluene, divinylbenzene, 1,1-diphenylethylene, or a combination thereof.
9. The separator for a rechargeable lithium battery according to claim 1, wherein In the second binder of the adhesive layer, the second unit is represented by Chemical Formula 2: [Chemical formula 2] In the chemical formula 2, R 3 is hydrogen, fluorine, substituted or unsubstituted C1 to C6 alkyl, or substituted or unsubstituted C6 to C20 aryl, and R 4 It is a C1 to C20 alkyl group.
10. The separator for a rechargeable lithium battery according to claim 1, wherein In the second binder of the adhesive layer, the third unit is represented by Chemical Formula 3: [Chemical formula 3] In the chemical formula 3, R 5 is hydrogen, fluorine, substituted or unsubstituted C1 to C6 alkyl, or substituted or unsubstituted C6 to C20 aryl, L 2 is carboxyl -C(=O)O-, carbonyl -C(=O)-, ether -O-, substituted or unsubstituted C1 to C6 alkylene, substituted or unsubstituted C3 to C10 cycloalkylene, substituted or unsubstituted C6 to C20 arylene, or a combination thereof, c is 0 or 1, and R 6 and R 7 are the same as or different from each other, and are each independently a substituted or unsubstituted C1 to C10 alkyl group, or a substituted or unsubstituted C6 to C20 aryl group.
11. The separator for a rechargeable lithium battery according to claim 1, wherein In the third unit of the second binder of the adhesive layer, the phosphonate monomer is acrylphosphonate.
12. The separator for a rechargeable lithium battery according to claim 1, wherein In the second binder of the adhesive layer, the copolymer includes 40 wt % to 80 wt % of the first unit, 5 wt % to 40 wt % of the second unit, and 0.1 wt % to 20 wt % of the third unit.
13. The separator for a rechargeable lithium battery according to claim 1, wherein The second binder of the adhesive layer is in the form of particles and has an average particle size D50 of 0.1 μm to 1 μm.
14. The separator for a rechargeable lithium battery according to claim 1, wherein The second binder of the adhesive layer is in the form of particles having a core-shell structure, and the shell includes the copolymer including the first unit derived from the vinyl aromatic monomer, the second unit derived from the alkyl acrylate, and the third unit derived from the phosphonate monomer.
15. The separator for a rechargeable lithium battery according to claim 1, wherein The second binder of the adhesive layer has a glass transition temperature of 60°C to 90°C.
16. The separator for a rechargeable lithium battery according to claim 1, wherein The swelling degree of the second binder of the adhesive layer is 600% to 1000%, and the swelling degree means the swelling degree after the second binder is left to stand in an electrolyte at 60° C. for 72 hours.
17. The separator for a rechargeable lithium battery according to claim 1, wherein The fluorine-based polymer of the third binder of the adhesive layer is polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene, polyvinylidene fluoride-tetrafluoroethylene, polyvinylidene fluoride-trifluoroethylene, polyvinylidene fluoride-chlorotrifluoroethylene, polyvinylidene fluoride-ethylene, or a combination thereof.
18. The separator for a rechargeable lithium battery according to claim 1, wherein The thickness of the adhesive layer is 0.05 μm to 3 μm.
19. A rechargeable lithium battery, comprising: Positive electrode; Negative electrode; The separator according to any one of claims 1 to 18, between the positive electrode and the negative electrode; as well as Electrolyte.
20. The rechargeable lithium battery according to claim 19, wherein: The positive electrode includes a positive electrode active material including a lithium nickel-based composite oxide, and a ratio of a nickel content of the lithium nickel-based composite oxide relative to a total content of metals excluding lithium is greater than or equal to 90 mol %.
Citation Information
Cited By
Battery diaphragm, preparation method thereof and lithium battery
CN121529114A
